Building the Croatian Morphological Lexicon - Tadić, Marko (Array, 2003)
The paper presents the work being done so far on the building of the Croatian Morphological Lexicon (CML). It has been collected since 2002 in the Institute of Linguistics, Faculty of Philosophy, University of Zagreb. The CML is planned to have two sub-lexicons: derivative/compositional and inflectional, both produced by a generator. The result of generation is lexicon as two distinct lists of generated combinations of morphemes and complete word-forms both with additional data that can be used in further processing. The inflectional component is presented more in detail in the second part of the paper. At the end, the several possible applications of CML are discussed.